Cytogenetics Analysis and Testis Morphology of Aquatic Species of the Families Belostomatidae, Gelastocoridae, Gerridae, Notonectidae, and Veliidae (Heteroptera). Issue 1 (22nd March 2015) - Vicente Pereira, Luis Lenin; Chaboli Alevi, Kaio Cesar; Urbanin Castanhole, Márcia Maria; Figueiredo Moreira, Felipe Ferraz; Freires Barbosa, Julianna; Massumi Itoyama, Mary
Abstract : The Heteroptera have holocentric chromosomes with kinetic activity restricted to the end of chromosomes. The first meiotic division is reductional for the autosomes and equational for the sexual. Only a few species of this suborder have been analyzed. In this study, we observed the morphologies of the testes of the Heteroptera species Belostoma anurum (Herrich-Schäffer, 1948), Belostoma micantulum (Stal, 1858), Gelastocoris angulatus (Melin, 1929), Gelastocoris flavus flavus (Guérin-Méneville, 1844), Rheumatobates crassifemur crassifemur (Esaki, 1926), Buenoa amnigenus (White, 1879), Buenoa unguis (Truxal, 1953), Martarega brasiliensis (Truxal, 1949), Martarega membranácea (White, 1879), Martarega uruguayensis (Berg, 1883), Rhagovelia tenuipes (Champion, 1898) and Rhagovelia zela (Drake, 1959). We found that the testes of these species can be round, round/spiral, or elongated/spiral. The size of the prophase I cells was found to vary, with the smallest ones being detected in B. micantulum and Rha. zela, the largest in G. f. flavus, and ones of intermediate size in R. c. crassifemur and M. brasiliensis . With respect to the chromosome complement, we verified the presence of 2 n = 16 (14A+XY, B. micantulum and G. angulatus ), 21 (20A+X0, R. c. crassifemur ), 23 (22A+X0, Rha. zela and Rha. tenuipes ), 25 (24A+X0, Bu. amnigenus and Bu. unguis; 22A+2m+X0, M. membranacea ), 27 (24A+2m+X0, M. brasiliensis and M. uruguayensis ), 29 (26A+X1 X2 Y, B. anurum ), and 35 (30A+X1 X2 X3 X4 Y, G. f. flavus ). We found that the features of spermatogenesis in these species are similar to those of other previously described Heteroptera species, differing only in testicular morphology, chromosome number, and sex chromosome system.